It Is Music to My Ears! Teaching English to High School Students Through Song - Maria-Romanița Camară; Adrian Naznean (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2022)
Songs have been used in teaching English as a foreign language for several decades with considerable positive results. The purpose of our study was to assess the benefits of using songs in the EFL classroom. The study was conducted throughout the first semester of academic year 2020-2021, precisely between the months October-January, at Samuil Micu High School of Sărmașu, Romania and involved two groups of participants. The participants were divided into the study group represented by students in class 10 B, while the control group consisted of students in class 10 A. Pre- and post-tests were administered to assess students’ knowledge of the investigated elements: grammar and vocabulary. Following the study, the post-test results of the study group were assessed and showed a significant increase in language acquisition. Keywords: ELT, Teaching Through Music, High School Student